2014
DOI: 10.1111/1574-6941.12273
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic fungal endophytes in theTriticeae- survey and description

Abstract: Grasses of the tribe Triticeae were screened to determine the presence of mutualistic epichloae fungal endophytes. Over 1500 accessions, from more than 250 species, encompassing 22 genera within the Triticeae were screened using immunodetection and direct staining/microscopy techniques. Only two genera, Elymus and Hordeum, were identified as harbouring epichloae endophytes with accessions native to a range of countries including Canada, China, Iran, Kazakhstan, Kyrgyzstan, Mongolia, Russia and the USA. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 90 publications
(123 reference statements)
0
28
0
2
Order By: Relevance
“…On 16 January 2013, approximately 100 tillers from T-NEA2 were immunoblotted and the endophyteinfected tillers DNA typed by a simple sequence repeat assay for endophyte strain (Card et al 2014).…”
Section: Herbage Measurementsmentioning
confidence: 99%
“…On 16 January 2013, approximately 100 tillers from T-NEA2 were immunoblotted and the endophyteinfected tillers DNA typed by a simple sequence repeat assay for endophyte strain (Card et al 2014).…”
Section: Herbage Measurementsmentioning
confidence: 99%
“…For instance, in the search for Epichlo€ e in tundra grasslands, where their presence causing reindeer grazing avoidance had been hypothesized (Br athen & Oksanen 2001), false positives were achieved for ten fungal endophyte species, and a total of 59 species were found (Jensen et al 2011). Moreover, Epichlo€ e in the wild is limited to two grass genera (Card et al 2014), hence the majority of grasses host other fungal endophytes than those belonging to the Epichlo€ e genus. The high richness and ubiquitous nature of fungal endophytes strongly suggests fungal endophyte species in general can influence plant herbivore interactions (Jensen et al 2011), whereas in what ways are still mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Karimi et al (2012) found that the host specificity of asexual Epichloë endophytes from Festuca arundinacea, F. pratensis, and Lolium perenne was consistent in geographically distant host grasses of the same species. However, Card et al (2014) analyzed endophytes isolated from Hordeum and Elymus species and found that most endophytes cluster according to geographical regions rather than host species. Our results were not consistent with either of the above findings.…”
Section: Endophytic Tubb + Tefa Treementioning
confidence: 99%
“…A previous study (Torabinejad and Mueller, 1993) found that the polyploid Elymus species in this study contain genomes of the St, H and Y types, potentially from Pseudoroegneria, Hordeum and an unknown species. Pseudoroegneria species do not contain endophytes (Card et al, 2014). The transmission of asexual Epichloë endophytes to the next generation generally occurs via seeds (White et al, 1993).…”
Section: Hypothesis Of Endophyte Distribution Based On Host Hybridizamentioning
confidence: 99%
See 1 more Smart Citation